Optimizing Filing Systems for Administrative Effectiveness: A Conceptual Review - Rade Nugraha; Siti Maratussholihah; Nasrun Harahap (ALFIHRIS : Jurnal Inspirasi Pendidikan, 2025)
Archive management is an important aspect in supporting administrative effectiveness and organizational continuity. This article discusses various archival concepts ranging from the definition of archives, storage systems and procedures, vertical and horizontal classification of archives, to the management of dynamic and static archives. In addition, it also discusses the importance of correspondence retention, archive maintenance, and archiving vital documents to ensure the security and accessibility of information. The method used in this study is a literature study by collecting and analyzing various sources related to archives. The results show that the implementation of a structured archiving system and proper procedures can improve work efficiency